PENGARUH THIN CAPITALIZATION DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK DENGAN PEMANFAATAN TAX HAVENS COUNTRY SEBAGAI VARIABEL MODERATING - Dewi, Rahmawati; Kusumawati, Nugrahini; Afiah, Efi Tajuroh; Nurizki, Aris Trismayadi (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of thin capitalization and transfer pricing on tax avoidance either partially or simultaneously. In addition, this study also aims to determine the effect of moderation between thin capitalization and transfer pricing with the use of tax havens countries on tax avoidance. This research was conducted on Multinational Companies Listed on the Indonesia Stock Exchange in 2019-2021. The method used in this research is correlational quantitative method. The population used in this study amounted to 116 (one hundred and sixteen) companies. Where the determination of the sample using purposive sampling method, in order to obtain a sample of 35 (thirty five) companies based on certain criteria. The data analysis in this study uses the moderate regression analysis method with a statistical program tool, namely Smart PLS Version 3.3.9. Based on the results of hypothesis testing, it shows that partially (1) Thin Capitalization has no significant effect on Tax Avoidance, (2) Transfer Pricing has a significant effect on Tax Avoidance and simultaneously (3) Thin Capitalization and Transfer Pricing have no effect on Tax Avoidance, and in moderation (4) Thin Capitalization by Utilizing Tax Havens Country to weaken Tax Avoidance, (5) Transfer Pricing by Utilizing Tax Havens Country strengthens Tax Avoidance. So, it can be concluded that partially only 1 (one) variable has a significant effect on tax avoidance and simultaneously there is no significant effect on tax avoidance, and in moderation only 1 (one) variable strengthens tax avoidance